Penerapan Pembelajaran Kooperatif Group Investigation dengan Media Gadget terhadap Keaktifan Siswa XI MIPA 4 SMA Negeri 4 Surakarta Tahun Pelajaran 2017/2018 - Azhari Fatikhasuri1; Slamet Santosa1; Suwarno Suwarno1; Tutut Sumarjiyana2 (Universitas Sebelas Maret, 2018)
The aim of this research to determine the implementation of group investigation with media gadget on student activeness XI MIPA 4 SMA Negeri 4 Surakarta year 2017/2018. Subjects in this study were students of SMA Negeri 4Surakarta class XIScience 4 with the number of 31 students.This research is classroom action research that refers to the Kemmis and Mc Taggart models that include planning, implementation, observation, and reflection activities in each cycle. The main data is the result of student activation observation during the learning process with cooperative group investigation learning model. Validation of data using triangulation method.Data analysis using qualitative descriptive consisting of three stages of data reduction, data presentation and drawing conclusion.This classroom action research is carried out in two cycles, with each cycle being two meetings. The results showed that group investigation cooperative learning model with media gadgetis able to improve the student activenessXI MIPA 4 SMA Negeri 4 Surakarta year 2017/2018 before action 41%, first cycle is 60%, second cycle is 78%.